Gender expression associated with BMI in a prospective cohort study of US adolescents. (27th January 2016) - Bryn Austin, S.; Ziyadeh, Najat J.; Calzo, Jerel P.; Sonneville, Kendrin R.; Kennedy, Grace A.; Roberts, Andrea L.; Haines, Jess; Scherer, Emily A.
Abstract : Objective: To examine the relationship between gender expression (GE) and BMI in adolescence. Methods: Repeated measures of weight‐related behaviors and BMI were collected from 1996 to 2011 via annual/biennial self‐report surveys from youth aged 10 to 23 years (6, 693 females, 2, 978 males) in the longitudinal Growing Up Today Study. GE (very conforming [referent], mostly conforming, nonconforming) was assessed in 2010/11. Sex‐stratified, multivariable linear models estimated GE group differences in BMI and the contribution of sexual orientation and weight‐related exposures to group differences. Models for males included interaction terms for GE with age. Results: In females, mostly conforming youth had 0.53 kg m −2 and nonconforming had 1.23 kg m −2 higher BMI; when adding adjustment for sexual orientation and weight‐related exposures, GE group estimates were attenuated up to 8% and remained statistically significant. In males, mostly conforming youth had −0.67 kg m −2 and nonconforming had −1.99 kg m −2 lower BMI (age [in years]) interactions were between −0.09 and −0.14 kg m −2 ; when adding adjustment for sexual orientation and weight‐related exposures, GE group estimates were attenuated up to 11% and remained statistically significant. Conclusions: GE is a strong independent predictor of BMI in adolescence. Obesity prevention and treatment interventions with youth must address ways that gender norms may reinforce or undermine healthful behaviors.